Behaviors of quenched polyampholytes in solution and gel state - Kudaibergenov, Sarkyt E.; Okay, Oguz (Wiley, 2020)
The quenched or strongly charged polyampholytes represent amphoteric macromolecules consisting of static positive and negative charges that slightly depend on pH. Here, the behavior of linear and cross‐linked quenched polyampholytes (QPA) in aqueous salt solutions is reviewed together with their stimuli‐responsive character as functions of temperature and ionic strength. The volume‐phase, swelling‐deswelling, self‐healing, viscoelastic, and mechanical properties of QPA gels are also discussed. Complexation of QPA with dye molecules, surfactants, and proteins is outlined. Application aspects of QPA cover biotechnology, biomedicine, oil recovery, desalination, etc.